Peran Keterlibatan Konsumen dalam Pembelian Aksesori Fotografi - Dewanti, Retno; Sebastian, Nicky Agathon; Rita, Rita (Binus Business Review, 2012)
Nowadays Consumer Involvement, in the midst of business competition, becomes an interesting topic to discuss. The level of consumer involvement can be based on the value and the needs felt by the consumers themselves. The purpose of this research is to analyze the influence of Promotional Mix and Situational Context toward the consumer involvement and its impact on the purchase decision on photography accessories. The data was gathered from a photography fan community. The method used on this research is Path Analysis in order for us to know about the purchase decision making based on two variables, they are, the indirect impact of promotional mix towards the purchase decision and the indirect impact of situational context towards the purchase decision. The analyzed data shows that, together, promotional mix and situational context are affecting the photography consumersâ involvement and they create an impact on photography accessories purchase decision.